CYP2D6 Genotype Phenotype Discordance Due to Drug‐Drug Interaction. Issue 5 (25th July 2018) - Monte, Andrew A.; West, Kelsey; McDaniel, Kyle T.; Flaten, Hania K.; Saben, Jessica; Shelton, Shelby; Abdelmawla, Farah; Bushman, Lane R.; Williamson, Kayla; Abbott, Diana; Anderson, Peter L.
Abstract : Drug‐drug interactions have been demonstrated to alter cytochrome 2D6 (CYP2D6) enzyme phenotype due to inhibitor ingestion, although it is unclear how substrate interactions affect phenotype. This was a pragmatic clinical trial examining the kinetics of a CYP2D6 enzyme probe drug with and without CYP2D6‐dependent substrates. Patients were enrolled into an inpatient study unit, and orally administered a 2 mg microdose of dextromethorphan (DM) to probe enzyme activity with and without CYP2D6‐dependent drug‐drug interactions. Thirty‐nine subjects were enrolled in this trial. Twelve subjects were on no CYP2D6‐dependent drugs and 27 were on one or more CYP2D6‐dependent drugs. There were 1 poor metabolizer, 5 intermediate metabolizers, 31 normal metabolizers, and 2 ultra‐rapid metabolizers. Those with co‐ingestion of another CYP2D6‐dependent drug were 9.49 (95% confidence interval (CI): 1.54–186.41; P  = 0.01) times more likely to have genotype‐phenotype discordance based upon the 3 hours dextrophan/dextromethorphan (DX/DM) ratio. CYP2D6 substrate co‐ingestions can cause genotype‐phenotype discordance.